Arthur packets for p-adic groups by way of microlocal vanishing cycles of perverse sheaves, with examples - Cunningham, Clifton; Fiori, Andrew; Moussaoui, Ahmed; Mracek, James; Xu, Bin (American Mathematical Society, 2022)
View the abstract.